The hard thing about hard things : - Horowitz, Ben (HarperCollins Publishers, 2014)
Ben Horowitz, co-founder of Andreessen Horowitz and one of Silicon Valley's most rspected and experienced entrepreneurs, offers essential advice on building and running a startup -- practical wisdom for managing the toughest problems business school doesn't cover, based on his popular Ben's Blog.